Mechanical properties of modern restorative “bioactive” dental materials - an in vitro study - Mateusz Radwanski; Ewa Zmyslowska-Polakowska; Karolina Osica; Michal Krasowski; Salvatore Sauro; Louis Hardan; Monika Lukomska-Szymanska (Scientific Reports)
Abstract This study aimed at assessing the mechanical properties and degradation of commercial bioactive materials. The bioactive materials (Activa Bioactive Restorative, Beautifil Flow Plus F00, F03, Predicta Bulk Bioactive) and composite resin Filtek Supreme Flow were submitted to flexural and diametral tensile strength tests (FS, DTS), modulus of elasticity (ME) evaluation, and analysis of aging in 70% ethanol and saliva on their hardness and sorption. The results for DTS ranged from 33.16 MPa (Beautifil Flow Plus F03) to 47.74 MPa (Filtek Supreme Flow). The highest FS was 120.40 MPa (Predicta Bulk Bioactive), while the lowest values were 86.55 MPa (Activa Bioactive Restorative). Activa Bioactive Restorative showed the lowest ME, as well as the highest water sorption both in alcohol and artificial saliva. Moreover, aging in saliva induced a significant decrease in hardness for Activa Restorative (p < .01). Alcohol storage caused a significant decrease in hardness for all materials (p < .0001). All tested materials met the basic requirements for light-curing materials in terms of DTS and FS. However, all materials showed higher sorption in alcohol than in saliva, while hardness decreased significantly after 30 days. Predicta Bulk Bioactive presented the highest mechanical parameters, initial hardness, and the lowest sorption of alcohol and saliva.